Novel Natural Oximes and Oxime Esters with a Vibralactone Backbone from the Basidiomycete Boreostereum vibrans. Issue 2 (13th January 2016) - Chen, He‐Ping; Zhao, Zhen‐Zhu; Li, Zheng‐Hui; Dong, Ze‐Jun; Wei, Kun; Bai, Xue; Zhang, Ling; Wen, Chun‐Nan; Feng, Tao; Liu, Ji‐Kai
Abstract: A variety of novel natural products with significant bioactivities are produced by the basidiomycete Boreostereum vibrans . In the present study, we describe 16 novel natural oximes and oxime esters with a vibralactone backbone, vibralactoximes, which were isolated from the scale‐up fermentation broth of B. vibrans . Their structures were determined through extensive spectroscopic analyses. These compounds represent the first oxime esters from nature. The hypothetical biosynthetic pathway of these compounds was also proposed. Seven compounds exhibited significant pancreatic lipase inhibitory activity, while ten compounds exhibited cytotoxicities against five human cancer cell lines (HL‐60, SMMC‐7721, A‐549, MCF‐7, and SW480), with IC50 values comparable with those of cisplatin. Abstract : Valuable vibralactoximes ! Sixteen vibralactoximes—novel oximes and oxime esters—were isolated from the scale‐up fermentation of the fungus Boreostereum vibrans . These compounds represent the first oxime esters from nature. Seven compounds showed significant pancreatic lipase inhibition, while ten had cytotoxicities towards five human cancer cell lines (HL‐60, SMMC‐7721, A‐549, MCF‐7, and SW480) comparable with cisplatin.